ปัจจัยที่มีอิทธิพลต่อการปฏิบัติการสอนในสถานศึกษาของนักศึกษา คณะศึกษาศาสตร์ สาขาวิชาการสอนภาษาไทย วิทยาลัยศาสนศาสตร์ยโสธร - คำแสน, จีรภา; (ศิลากุล), พระมหานพรัตน์ ขนฺติธมฺโม; แสนสิ่ง, พีรพงษ์ (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 1 No 2 (2024): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 1 ฉบับที่ 2 : พฤษภาคม - สิงหาคม 2567, 2024)
The objective of this research is to study the problems and factors influencing the success of teaching practice among fourth-year students majoring in Thai Language Education at the Faculty of Education for the academic year 2023. The findings and recommendations from the research will be integrated and applied to the management of teaching and the practical training of these students. The target group consists of 50 students. The statistics used in the research include percentage, mean, and standard deviation. The results revealed that the problems in teaching practice included inadequate teaching materials, which was rated at a high level (µ = 4.40); an unproductive classroom environment for organizing activities, rated at a high level (µ = 4.36); and planning and the role of the teacher, rated at a high level (µ = 4.30). The factors contributing to the success of teaching practice included patience, understanding, and attentiveness towards students, which were rated at the highest level (µ = 4.65); knowledge, expertise, and experience of the trainee, rated at a high level (µ = 4.41); and creativity and problem-solving ability, rated at a high level (µ = 4.38), respectively. The recommendations for improvement include continuously inspiring student teachers, close supervision by faculty and mentor teachers, real-world assessment of teaching practice, and rewarding achievements.